Maximal dexterous trajectory generation and cubic spline optimization for fully planar parallel manipulators. (November 2016) - Kucuk, Serdar
Highlights: The new algorithm efficiently generates collision, singularity and interference-free maximal dexterous trajectory PSO algorithm is successful at producing time optimal trajectory planning for robotic manipulators. Only two working modes (WM1 and WM8 ) of 3-DOF RRR FPPM have acceptable dexterous regions where robot manipulator works effectively. Abstract: In this study, a new numerical algorithm is developed to generate the collision, singularity and interference-free maximal dexterous workspace for F ully P lanar P arallel M anipulators (FPPM s). A scheduling algorithm is also added to P roposed N umerical A lgorithm (PNA ) in order to find the best trajectory in terms of dexterity between two points in the developed maximal dexterous workspace. Among the polynomial splines, cubic spline used commonly for interpolating robotic trajectories is preferred also in this study. P article S warm O ptimization (PSO ) algorithm is used for cubic spline optimization in order to have time optimal smooth motion that is the basic requirement of trajectory generation. Simulation results illustrated that (i) PNA is an efficient algorithm to generate collision, singularity and interference-free maximal dexterous trajectory and (ii) PSO algorithm is successful at producing time optimal trajectory planning for robotic manipulators. Graphical abstract: